Donor Specific Anti-HLA Antibody and Risk of Graft Failure in Haploidentical Stem Cell Transplantation - Piyanuch Kongtim; Kai Cao; Stefan O. Ciurea (Advances in Hematology)
Outcomes of allogeneic hematopoietic stem cell transplantation (AHSCT) using HLA-half matched related donors (haploidentical) have recently improved due to better control of alloreactive reactions in both graft-versus-host and host-versus-graft directions. The recognition of the role of humoral rejection in the development of primary graft failure in this setting has broadened our understanding about causes of engraftment failure in these patients, helped us better select donors for patients in need of AHSCT, and developed rational therapeutic measures for HLA sensitized patients to prevent this unfortunate event, which is usually associated with a very high mortality rate. With these recent advances the rate of graft failure in haploidentical transplantation has decreased to less than 5%.